2009
DOI: 10.1088/0004-637x/698/1/43
|View full text |Cite
|
Sign up to set email alerts
|

JET BREAKS AND ENERGETICS OFSwiftGAMMA-RAY BURST X-RAY AFTERGLOWS

Abstract: We present a systematic temporal and spectral study of all Swift -XRT observations of GRB afterglows discovered between 2005 January and 2007 December. After constructing and fitting all light curves and spectra to power-law models, we classify the components of each afterglow in terms of the canonical X-ray afterglow and test them against the closure relations of the forward shock models for a variety of parameter combinations. The closure relations are used to identify potential jet breaks with characteristi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
397
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 309 publications
(447 citation statements)
references
References 111 publications
42
397
3
1
Order By: Relevance
“…The optical/NIR temporal index α = −0.73 ± 0.01 of the segment a is consistent within 3σ errors with the closure relations (Granot & Sari 2002;Dai & Cheng 2001;Zhang & Mészáros 2004;Racusin et al 2009) for a normal decay in the ν m < ν < ν c regime, where the jet is interacting with a homogeneous ISM and is in the slow cooling phase. The corresponding power-law index of electron energy distribution p = 1.44 ± 0.16 is very hard.…”
Section: Closure Relationssupporting
confidence: 80%
“…The optical/NIR temporal index α = −0.73 ± 0.01 of the segment a is consistent within 3σ errors with the closure relations (Granot & Sari 2002;Dai & Cheng 2001;Zhang & Mészáros 2004;Racusin et al 2009) for a normal decay in the ν m < ν < ν c regime, where the jet is interacting with a homogeneous ISM and is in the slow cooling phase. The corresponding power-law index of electron energy distribution p = 1.44 ± 0.16 is very hard.…”
Section: Closure Relationssupporting
confidence: 80%
“…Since Dainotti, Cardone & Capozziello (2008) have shown a correlation between the luminosity at the end of the X-ray plateau with the time the plateau phase ceases, we examined whether the plateau phase plays a role in our correlation. In our sample we find 35 GRBs that have a plateau following the criteria of Racusin et al (2009). Repeating the Spearman rank correlation for log LX,200s − αX,>200s for these GRBs, we find a coefficient of -0.73 at a confidence of 4.97σ, indicating a strong correlation.…”
Section: Observational Resultssupporting
confidence: 56%
“…In order to compare the afterglow properties with the prompt emission properties we determined the isotropic γ-ray energy Eiso and peak energy, E peak from the γ-ray emission, following Racusin et al (2009). The BAT fluence was converted to Eiso at a rest-frame bandpass of 10 to 10000 keV using equation 4 from Bloom, Frail & Sari (2001).…”
Section: Grb Afterglow Samplementioning
confidence: 99%
“…3, given the wide range of measurements determined from slope changes in LGRB afterglow light curves (see, e.g., Racusin et al 2009). Unfortunately, recent simulations have shown that this change in the afterglow light curve may occur at much later times than currently thought, and therefore, the change in the light curve that we currently observe is not in fact due the result of the jet opening angle (van Eerten & MacFadyen 2012).…”
Section: Model Limitationsmentioning
confidence: 99%